An Evaluation of Fashion Involvement in the Context of Sustainable Consumption Behavior - ÖZTAY, Hilal (Kastamonu University, 2023)
This study aims to examine fashion involvement in the context of sustainable consumption behavior. The dimensions of sustainable consumption behavior were determined and the effects of these dimensions on fashion involvement were investigated. Furthermore, the moderation effect of gender on these variables was analyzed. A quantitative research approach was adopted and descriptive, exploratory, and confirmatory statistical analyses were conducted. Hypothesis testing techniques were used to decide whether to accept or reject the hypothesis. The results show that household energy saving and responsive food choice have a significant effect on fashion involvement and gender has a moderator effect between these dimensions and fashion involvement. For male consumers, fashion involvement increases when responsive food choice behaviors increase and decrease when fashion involvement decreases. Female consumers who try to conserve energy resources at home are less interested in fashion and fashion-related activities. The originality of this study is that it attempts to explore the relationship between two concepts that do not seem directly related and to evaluate all consumption practices in daily life with a holistic view.
Keywords: Sustainability; Sustainable Consumption Behavior; Fashion Involvement; Public Relations; Halkla İlişkiler; Sürdürülebilirlik; Sürdürülebilir Tüketim Davranışı; Moda İlgilenimi; 11. Sustainability; 7. Clean energy; 12. Responsible consumption